Kebebasan Beragama Dan Berkeyakinan Dalam Negara Hukum Indonesia: Dualisme Tafsir Konseptual Dan Putusan Mahkamah Konstitusi - Sanjaya, Dixon; Rahim, Akhlish Aulia (UI Scholars Hub, 2024)
Religious life in Indonesian state of law is still faced with friction and instability. This is due to dualism of interpretation of constitutional norms, differences in human rights perspectives on the freedom of religion and belief, and conflicts over statutory regulations. This research analyzes the concept of freedom of religion and belief (Religious Freedom) by conceptually exploring the discourse on relationship between religion and state and mapping the Constitutional Court's decision on commitment of the Religious Freedom. Normative juridical research is carried out using case, historical, and conceptual approaches. The finding is that relationship between state and religion is conceptually dichotomous between the ideas of the founding fathers who wanted limited separation and the ideas of legal experts in modern era who wanted a more active role for the state towards religion in administering the state. These two concepts result in religious fragmentation in society which underlies the dominant attitude of majority over minorities. Meanwhile, Constitutional Court's commitment to Religious Freedom experienced a dualism between strong commitment (judicial activism) and weak commitment (judicial restraint) which resulted in the realization of freedom of religion and belief facing systemic and cultural problems that couldn’t be realized optimally. A paradigm shift is needed from Constitutional Court, government, and society to act independently and move away from majority perspective to present meaningful concept of equality for Religious Freedom with an understanding of moderation and religious pluralism not based on narrow fanaticism.